The Structure of Rhythm in Prose Poetry: The Experience of Ammar Al-Masoudi in "Brown Summer" (A Model) - Dr.Jameel Sahib Jaleel (مجلة اداب ذي قار, 2025)
This paper sheds light on an exciting experience related to rhythm in prose poetry. It specifically addresses the rhythm in prose texts to show how it can be exciting, distinctive, and innovative, and how this rhythm contributes to revealing the creative structure of the prose text. The study concluded with several results that clarify the main characteristics of the prose text, such as rhythmic totality, rhythmic cohesion, and rhythmic differences.